A Pilot Study of a Peer-Group Lifestyle Intervention Enhanced With mHealth Technology and Social Media for Adults With Serious Mental Illness. Issue 6 (June 2016) - Aschbrenner, Kelly A.; Naslund, John A.; Shevenell, Megan; Kinney, Elizabeth; Bartels, Stephen J.
Abstract : Abstract: This pilot study examined the preliminary effectiveness of a peer-group lifestyle intervention enhanced with mobile health technology and social media for obese individuals with serious mental illness. Thirty-two participants with a body mass index of 30 or higher received a 24-week intervention designed to facilitate peer support for lifestyle change through experiential learning and use of wearable activity tracking devices, smartphone applications, and Facebook to reinforce physical activity, healthy eating, and group participation between sessions. The primary outcome was weight loss. Secondary measures included fitness and participants' perceptions of peer-group support. Most participants (72%) lost weight, including 28% achieving clinically significant weight loss, and 17% of participants showed clinically significant improvements in cardiovascular fitness. Weight loss was associated with perceived peer-group support. This evaluation demonstrated the preliminary effectiveness of a potentially scalable peer-group lifestyle intervention delivered in community mental health settings for obese individuals with serious mental illness.